Homeobox A4 suppresses vascular remodeling by repressing YAP/TEAD transcriptional activity. (9th March 2020) - Kimura, Masahiro; Horie, Takahiro; Baba, Osamu; Ide, Yuya; Tsuji, Shuhei; Ruiz Rodriguez, Randolph; Watanabe, Toshimitsu; Yamasaki, Tomohiro; Otani, Chiharu; Xu, Sijia; Miyasaka, Yui; Nakashima, Yasuhiro; et al.
Abstract: The Hippo signaling pathway is involved in the pathophysiology of various cardiovascular diseases. Yes‐associated protein (YAP) and transcriptional enhancer activator domain (TEAD) transcriptional factors, the main transcriptional complex of the Hippo pathway, were recently identified as modulators of phenotypic switching of vascular smooth muscle cells (VSMCs). However, the intrinsic regulator of YAP/TEAD‐mediated gene expressions involved in vascular pathophysiology remains to be elucidated. Here, we identified Homeobox A4 (HOXA4) as a potent repressor of YAP/TEAD transcriptional activity using lentiviral shRNA screen. Mechanistically, HOXA4 interacts with TEADs and attenuates YAP/TEAD‐mediated transcription by competing with YAP for TEAD binding. We also clarified that the expression of HOXA4 is relatively abundant in the vasculature, especially in VSMCs. In vitro experiments in human VSMCs showed HOXA4 maintains the differentiation state of VSMCs via inhibition of YAP/TEAD‐induced phenotypic switching. We generated Hoxa4‐deficient mice and confirmed the downregulation of smooth muscle‐specific contractile genes and the exacerbation of vascular remodeling after carotid artery ligation in vivo . Our results demonstrate that HOXA4 is a repressor of VSMC phenotypic switching by inhibiting YAP/TEAD‐mediated transcription. Synopsis: HOXA4 suppresses vascular smooth muscle cell phenotypic switching and vascular remodeling by inhibiting YAP/TEAD‐mediated transcription. Unbiased shRNA screen identified HOXA4 as a repressor of YAP/TEAD transcriptional activity. HOXA4 competes with YAP for binding to TEADs to preserve VSMC differentiation. Hoxa4 ‐deficient mice showed exacerbated neointima formation after carotid artery ligation. Abstract : HOXA4 suppresses vascular smooth muscle cell phenotypic switching and vascular remodeling by inhibiting YAP/TEAD‐mediated transcription.